(untitled) (Research, Society and Development, 2022)
As of 2019, in the municipality of Nova Xavantina, rural schools located in rural settlements are no longer offered by the government, causing excessive damage to the local community. This article refers to the study under development in the scope of the Postgraduate course that deals with the closing of the Tamboril II Municipal School and aims to analyze, from the narratives of protagonists who lived this experience, the political and pedagogical implications perceived by education professionals, identifying the action of municipal managers in the conduction of public policies. The research with a historical bias and qualitative approach makes use of documentary sources and testimonies of professionals who worked at the school in the period that it was deactivated. As a result, it can be said that there were impacts on the professional and personal lives of some civil servants, and on the part of municipal managers a counter-policy to the detriment of settlers and the school community, in the name of cutting costs that, over time, can prove extremely harmful to peasants.